The impact of COVID-19 on Finnish football clubs - Liikanen, M. (Vaasa University of Applied Sciences, 2022)
In this thesis the impact of the coronavirus pandemic on Finnish football clubs and how the pandemic has affected the clubs in terms of business is investigated. The purpose of the research is to discover new ways for Finnish football clubs to develop their business operations after the pandemic. The thesis is a literature review. Firstly, Finnish football and its business features is presented in general terms. Secondly, different areas of sports management is researched and finally, towards the end of the paper, the impact of the coronavirus pandemic on the event industry in general will be reviewed. As research material interviews as well as various companies` financial statements will be used. The study conducted in this thesis indicates that the impact of coronavirus pandemic on Finnish football clubs has been enormous. The cashflow of the companies decreased significantly, especially during the first year of the pandemic. However, by adapting the business models to the situation, the clubs could decrease the negative impact of coronavirus pandemic.